2016
DOI: 10.2139/ssrn.2803170
|View full text |Cite
|
Sign up to set email alerts
|

Intended College Enrollment and Educational Inequality: Do Students Lack Information?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 19 publications
0
37
1
Order By: Relevance
“…In contrast to the results ofPeter and Zambre (2017), who show that the information workshop affects students from different educational backgrounds differently in the short run, the longer run effects of the information workshop do not differ significantly by students' educational background.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the results ofPeter and Zambre (2017), who show that the information workshop affects students from different educational backgrounds differently in the short run, the longer run effects of the information workshop do not differ significantly by students' educational background.…”
contrasting
confidence: 99%
“…Evidence for a presumably stronger impact on students with intentions to enroll is found by a previous study based on earlier waves of the panel we use. Peter and Zambre (2017) show that the information workshop affected students' intentions one year later. This treatment effect mainly works through stabilizing non-college background students' post-secondary educational plans.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, in the U.S., Avery and Kane (2004) found that there was only a weak connection between students' estimations of net returns from higher education and plans to attend college. However, there is also evidence that information interventions are efficient in changing beliefs about cost or returns from higher education and intentions to attend (Bleemer & Zafar, 2018;Oreopoulos & Dunn, 2012;Peter & Zambre, 2017). One study found that providing additional information about grants did not change college intentions but did increase college application behaviors (Ehlert, Finger, Rusconi, & Solga, 2017).…”
Section: Graduationmentioning
confidence: 99%
“…Existing studies for Europe indicate that the availability of information on possible career paths and educational investments tend to improve transitions into the labor market (Saniter et al, 2019;Peter and Zambre, 2017;Boockmann and Nielen, 2016) [Germany], Hoest et al (2013) [Denmark], and Borghans et al (2015) [Netherlands]. As a methodological aspect, which proves important for our study, Borghans et al (2015) show that variation in the take-up of counseling across schools is strong, which the study uses to instrument individual counseling.…”
Section: Introductionmentioning
confidence: 88%